An Assessment of Spelling and Typographical Errors in WebOPAC of Academic Libraries. Issue 1 (2nd June 2022) - Kumar, Vinit; Maurya, Sharad; Ji, Gopal
Abstract: WebOPAC serves as a discovery tool to let users discover and ascertain the availability of an item in the stacks of a library. To make searching more efficient and effective there is a need to eliminate the typographical errors which may be present in library catalogue. Typographical errors in the bibliographic data are of high concern as it affects the discoverability of items. Similarly, the identification of erroneous records is a challenge in large bibliographic databases. The present work attempts to assess the typographical errors in the WebOPAC of Sayajirao Gaekwad Library of Banaras Hindu University using Terry Ballard's typographical error terms list. Simple random sampling is used to select a hundred terms from each section of Ballard's list. The WebOPAC was searched to find matched erroneous records. The findings of the study showed that out of 500 queried erroneous terms, 131 terms retrieved 889 records averaging an overall rate of 6.78 erroneous records per error. Moreover, a part-of-speech wise analysis showed that most errors in the bibliographic records were found to be in the case of nouns and proper nouns, while the least records were retrieved for technical terms. The study has implications for libraries wishing to improve the quality of the bibliographic data in the records of their WebOPACs.